FPGA Based Hardware-in-the-Loop (HIL) Simulation of Induction Machine Model - Duman, Erkan; Can, Hayrettin; Akin, Erhan (Ieee, 2014)
The developed Hardware-in-the-Loop (HIL) Simulation was used to evaluate the performance of the electrical machinery driver systems in some cases which are very difficult or impossible to be tested in laboratory environment. By using this simulation environment, Embedded Control Systems (ECS) can easily be tested in a practically, cheaply and unhazardous way. In this study, we have developed a novel FPGA-based model of an induction machine in a single-chip in order to use in real-time simulation applications. In development steps, we have chosen Altera tools and used floating-point number system in model equations. The cycle time of the developed HIL Simulation environment is less than the previous studies thanks to FPGA based system modeling. According to the clock source of the development FPGA board, its value is about 1 microsecond.
16th International Power Electronics and Motion Control Conference and Exposition (PEMC) -- SEP 21-24, 2014 -- Antalya, TURKEY
Keywords: HIL Simulation; FPGA Implementation; Real Time Modelling; Induction Machine Model